The truth of the cry. Towards an archaeology of subjectivity (Nóema, 2013)
Aim of this paper is a survey of two thresholds of the subjectivity: infancy and animality. Children and animals share their condition of “subjected”: if the adult is a complete subject, the child is going to become and the animal is treated as an opposite pole as to subjectivity (or alternatively, but it is the same, as a surrogate subject). The starting point is the question: “What is a child?”; this apparently Socratic question sets out to sep the foundations of knowledge deposited on the common sense that considers the “real nature” of the subject.
Keywords: Infancy; memory; ethology; theriomorphism; animal; border